2014
DOI: 10.1002/phy2.277
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase 4 does not regulate collecting duct water and sodium handling

Abstract: Adenylyl cyclase (AC)‐stimulated cAMP is a key mediator of collecting duct (CD) Na and water transport. AC isoforms 3, 4, and 6 are expressed in the CD. Our group demonstrated that AC6, but not AC3, is involved in regulating CD Na and water transport. However, the role of AC4 in such regulation remains unknown. Therefore, we generated mice with loxP‐flanked critical exons in the Adcy4 gene and bred with mice expressing the aquaporin‐2/Cre recombinase transgene to yield CD principal cell‐specific knockout of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1). AC6 is the principal AC mediating these responses, as only AC6-deficient mice have urine concentration defects (54,55,118,122). However, cAMP-independent mechanisms for AQP2 trafficking also exist, as previously demonstrated, e.g., stimulation of prostanoid receptors EP2 and EP4 and short-term exposure to peroxisomal proliferator-activated receptor subtype ␥-agonist (102,111).…”
Section: Vasopressin-regulated Aqp2mentioning
confidence: 80%
“…1). AC6 is the principal AC mediating these responses, as only AC6-deficient mice have urine concentration defects (54,55,118,122). However, cAMP-independent mechanisms for AQP2 trafficking also exist, as previously demonstrated, e.g., stimulation of prostanoid receptors EP2 and EP4 and short-term exposure to peroxisomal proliferator-activated receptor subtype ␥-agonist (102,111).…”
Section: Vasopressin-regulated Aqp2mentioning
confidence: 80%
“…Previous studies have ruled out the involvement of AC3 and AC4 in the vasopressin-dependent stimulation of cAMP (21,22) and suggested that the most likely AC involved is AC6 (42), which is the most abundant AC in the CD. However, the present study did not allow defining which of the ACs is involved in the V2R-dependent stimulation of renin in the CD.…”
Section: Discussionmentioning
confidence: 99%
“…A tissue-specific knockout of AC4 has been generated for loss of expression in kidney collecting duct principal cells. AC4 does not appear to play a role in water and sodium handling in kidney Pharmacological Modulation of Mammalian Adenylyl Cyclases (Kittikulsuth et al, 2014a). Phenotypes from other tissues have not yet been reported.…”
mentioning
confidence: 96%